Zinc-bromine flow battery functional diaphragm as well as preparation method and application thereof

By alternately setting positive and negative coatings on the porous separator of zinc bromine flow batteries, the problems of bromine molecules penetration and oxidation corrosion are solved, the separator performance and service life of the battery are improved, and the coulomb efficiency and energy efficiency of the battery are improved. .

CN119133499AInactive Publication Date: 2024-12-13INST OF WENZHOU ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411622238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In practical applications, zinc bromine flow batteries face problems of bromine molecules penetration and oxidation corrosion, resulting in reduced self-discharge and Coulomb efficiency, and the existing modification methods have limited effects.

Method used

A negatively charged porous separator is used, and multiple positive and negatively charged coatings are alternately arranged on the outside of it. The coating is fixed by electrostatic action to form a zinc bromine flow battery functional separator to reduce the risk of bromine molecules penetration.

Benefits of technology

It effectively improves the separator performance and service life of zinc-brominated flow batteries, reduces the risk of electrolyte penetrating blind holes, and improves the balun efficiency and energy efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133499A_ABST
    Figure CN119133499A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-bromine flow battery functional diaphragm and a preparation method and application thereof.The zinc-bromine flow battery functional diaphragm comprises a porous diaphragm with negative electricity, a plurality of first coatings and a plurality of second coatings, the first coatings and the second coatings are alternately arranged on the outer side of the porous diaphragm, the first coatings are positively charged, and the second coatings are negatively charged; the outermost layer of the zinc-bromine flow battery functional diaphragm is the second coating, and the sum of the number of the first coating and the number of the second coating is not less than 2. The zinc-bromine flow battery functional diaphragm disclosed by the invention is spontaneously assembled layer by layer through the porous diaphragm with negative electricity, the first coating with positive electricity and the second coating with negative electricity, realizes effective connection and fixation through electrostatic interaction, and resists long-term repeated washing of electrolyte in the running process of a galvanic pile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of liquid flow batteries, and specifically to a zinc-bromine liquid flow battery functional diaphragm, a preparation method and application thereof. Background Art

[0002] In recent years, due to the instability and discontinuity of new energy generation technologies such as wind and solar energy, large-scale energy storage technologies based on flow batteries have developed rapidly. Zinc-bromine flow batteries have long been considered to be highly competitive in large-scale energy storage technologies due to their high energy density and low cost.

[0003] Although zinc-bromine flow batteries show great application potential in theory, they have encountered some scientific and technological difficulties in actual application. Among them, the positive electrode side still needs to face the problems of bromine molecule penetration and bromine molecule oxidation corrosion. On the positive electrode side of the battery, the bromide ions in the electrolyte will migrate to the positive electrode during charging, and the bromine ions will lose electrons on the surface of the positive electrode to form bromine element. However, bromine element is extremely corrosive and penetrating, and under the stimulation of the concentration gradient, bromine molecules will penetrate the diaphragm and migrate to the negative electrode side of the battery, reacting with the generated zinc element, causing the battery to self-discharge, thereby reducing the coulombic efficiency of the battery.

[0004] Many solutions have been proposed to solve the problem of bromine molecule penetration at the positive electrode, mainly including adding bromine molecule complexing agents to the electrolyte, modifying the positive electrode material, and modifying the battery separator. Among them, modifying the separator surface is an effective way, that is, improving the bromine barrier capacity of the battery separator is the most direct way. Through continuous research and development, the modified separator technology is expected to further promote the commercialization of zinc-bromine flow batteries. Summary of the invention

[0005] The purpose of this application is to improve the diaphragm performance of zinc-bromine liquid flow batteries and increase the service life of zinc-bromine liquid flow batteries.

[0006] To achieve the above objectives, the technical solution adopted in the present application is: to provide a zinc-bromine liquid flow battery functional diaphragm, including a negatively charged porous diaphragm, and a plurality of first coatings and a plurality of second coatings alternately arranged on its outer side, wherein the first coating is positively charged and the second coating is negatively charged, and the outermost layer of the zinc-bromine liquid flow battery functional diaphragm is the second coating, and the sum of the number of the first coating and the second coating is not less than 2.

[0007] As a preferred embodiment, the porous membrane is subjected to plasma treatment, ozone treatment, ultraviolet light treatment or mixed acid pickling treatment to make it negatively charged, thereby obtaining the negatively charged porous membrane.

[0008] As another preference, the sum of the number of the first coating layer and the number of the second coating layer is 2-30.

[0009] Provided is a method for preparing a functionalized diaphragm for a zinc-bromine liquid flow battery, comprising the following preparation steps: S1: pre-treating a porous diaphragm to form a porous diaphragm with negative charge; S2: preparing a polycationic polymer solution and a polyanionic polymer solution, immersing the porous diaphragm with negative charge in the polycationic polymer solution, and forming a first coating after drying; S3: immersing the porous diaphragm having the first coating in the polyanionic polymer solution, and forming a second coating after drying; S4: repeating the steps S2 and S3 as required to form a plurality of alternating first coatings and second coatings, and the outermost layer is the second coating, and freeze-drying to obtain the functionalized diaphragm for a zinc-bromine liquid flow battery.

[0010] As another preferred embodiment, the porous membrane is made negatively charged by any method of plasma treatment, ozone treatment, ultraviolet light treatment or mixed acid pickling to form the negatively charged porous membrane.

[0011] As another preference, the polycationic polymer solution is a solution of the following substances: polyaniline, polyethyleneimine, polydiallyldimethylammonium chloride, polypyrrole, chitosan.

[0012] As another preference, the polyanion polymer solution is a solution of the following substances: tannic acid, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyamic acid, polyamic acid salt, perfluorosulfonic acid, polystyrene sulfonate, polyarylether sulfone sulfonate, polyarylether sulfone ketone sulfonate.

[0013] As another preference, the mass fraction of the solute in the polycationic polymer solution is 1-30%, and the mass fraction of the solute in the polyanionic polymer solution is 1-30%.

[0014] As another preference, in step S1, the porous membrane is cleaned to obtain a pretreated porous membrane, and the pretreated porous membrane is made negatively charged to form the negatively charged porous membrane.

[0015] Provided is a zinc-bromine liquid flow battery, comprising the above-mentioned zinc-bromine liquid flow battery functionalized diaphragm, or the zinc-bromine liquid flow battery functionalized diaphragm prepared by the above-mentioned preparation method.

[0016] Compared with the prior art, the beneficial effects of this application are: (1) The zinc-bromine flow battery functional diaphragm of the present application is self-assembled layer by layer through a negatively charged porous diaphragm, a positively charged first coating layer and a negatively charged second coating layer, and is effectively connected and fixed through electrostatic action, thereby resisting long-term repeated scouring of the electrolyte during the operation of the battery stack; (2) In the steps of forming the first coating layer and the second coating layer, the functional diaphragm of the zinc-bromine flow battery of the present application adopts an ultrasonic-assisted mixed liquid impregnation method, which can help the solution enter the pores of the porous diaphragm, and the charged polymer electrolyte is adsorbed in the pores by electrostatic action, thereby reducing the proportion of blind holes; (3) The zinc-bromine liquid flow battery functional diaphragm of the present application can reduce the average pore size and blind hole ratio of the diaphragm, thereby reducing the risk of electrolyte penetrating the blind holes of the liquid flow battery diaphragm during repeated charging and discharging of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the pore size distribution diagram of the functional membrane of the liquid flow battery in Example 5 tested by the capillary method.

[0018] Figure 2 This is the pore size distribution diagram of the flow battery membrane of comparative example 3 tested by capillary method.

[0019] Figure 3 This is the pore size distribution diagram of the functional membrane of the liquid flow battery in Example 5 tested by mercury intrusion testing.

[0020] Figure 4 This is the pore size distribution diagram of the flow battery diaphragm of comparative example 3 tested by mercury intrusion method.

[0021] Figure 5 This is the pore size distribution diagram of the gas-liquid method test of the functional membrane of the liquid flow battery in Example 5.

[0022] Figure 6 This is the pore size distribution diagram of the liquid flow battery membrane of comparative example 3 tested by the gas-liquid method.

[0023] Figure 7 This is the pore size distribution diagram of the liquid-liquid method test of the functional membrane of the liquid flow battery in Example 5.

[0024] Figure 8 This is the pore size distribution diagram of the liquid-liquid method test of the liquid flow battery membrane of comparative example 3.

[0025] Fig. 9 This is a surface electron microscope image of the functional diaphragm of the liquid flow battery in Example 5.

[0026] Fig.10 This is the surface electron microscope image of the liquid flow battery membrane of comparative example 3. DETAILED DESCRIPTION

[0027] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0028] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0029] The present application provides a zinc-bromine liquid flow battery functional diaphragm, comprising a negatively charged porous diaphragm, and a first coating and a second coating alternately arranged on the outer side thereof, wherein the first coating is positively charged, the second coating is negatively charged, and the outermost layer of the negatively charged porous diaphragm is arranged as the second coating, and at least one layer of the first coating and the second coating is arranged.

[0030] The porous membrane is treated with plasma, ozone, ultraviolet light or mixed acid pickling to make it negatively charged, thereby obtaining a negatively charged porous membrane.

[0031] The zinc-bromine flow battery functional diaphragm of the present application is achieved by arranging an alternating first coating and a second coating on a negatively charged porous diaphragm, wherein the first coating is positively charged and the second coating is negatively charged. The first coating and the second coating can be effectively anchored by electrostatic action to resist long-term repeated scouring of the electrolyte during the operation of the battery stack.

[0032] In addition, the outermost layer of the multifunctional diaphragm of the zinc-bromine flow battery designed in this application is a negatively charged second coating, which will have a "like-charge repulsion" effect and can better block the Br formed by the self-complexation of bromine molecules in the positive electrode of the battery. 3- Br 5- The penetration of ions can improve the coulombic efficiency of the battery.

[0033] The present application arranges an alternating first coating and a second coating on the outside of a negatively charged porous membrane, and adopts a layer-by-layer self-assembly technology, which can conveniently control the total number of outer coating layers, thereby regulating the thickness of the zinc-bromine liquid flow battery membrane and even adjusting the pore size of the membrane, which can further realize the bromine barrier effect of the membrane and improve the coulombic efficiency of the liquid flow battery.

[0034] The present application provides a method for preparing a multifunctional diaphragm for a zinc-bromine flow battery, comprising the following preparation steps: S1: pre-treating the porous membrane to form a porous membrane with negative charge; S2: preparing a polycationic polymer solution and a polyanionic polymer solution, immersing the negatively charged porous separator in the polycationic polymer solution, and forming a first coating after drying; S3: immersing the porous separator having the first coating layer in a polyanionic polymer solution, and forming a second coating layer after drying; S4: Repeat steps S2 and S3 as needed to alternately form multiple layers of the first coating and the second coating, freeze-dry the porous diaphragm with the second coating as the outermost layer to obtain a zinc-bromine liquid flow battery functional diaphragm of the present application.

[0035] In some embodiments, the porous membrane may be negatively charged by plasma treatment, ozone treatment, ultraviolet light treatment, mixed acid pickling, etc. Furthermore, the mixed acid pickling is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.

[0036] The zinc-bromine liquid flow battery functional diaphragm of the present application is treated to be negatively charged before being impregnated with a polycationic polymer solution and a polyanionic polymer solution, and is effectively fixedly connected with a first coating layer with a positive charge, while the first coating layer with a positive charge is effectively fixedly connected with a second coating layer with a negative charge, and the porous diaphragm is fixed to the first coating layer and the second coating layer on its outer side through electrostatic action in a reciprocating cycle, and can resist repeated flushing of the electrolyte during the operation of the battery stack, thereby providing a structural basis for long-term energy storage of zinc-bromine liquid flow batteries.

[0037] In some embodiments, the porous membrane is first cleaned to obtain a pretreated porous membrane, and the pretreated porous membrane is treated to make it negatively charged. Furthermore, the porous membrane is ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water in sequence, and dried to obtain a pretreated porous membrane, and the pretreated porous membrane is modified to make it negatively charged.

[0038] In some embodiments, the polycationic polymer solution is hydrophilic, including but not limited to solutions of polyaniline, polyethyleneimine, polydiallyldimethylammonium chloride, polypyrrole, and chitosan.

[0039] In some embodiments, the polyanionic polymer solution is hydrophilic, including but not limited to solutions of tannic acid, polyacrylic acid, polyacrylic acid salts, polyacrylamide, polyamic acid, polyamic acid salts, perfluorosulfonic acid, polystyrene sulfonate, polyarylether sulfone sulfonate, polyarylether sulfone ketone sulfonate.

[0040] In some embodiments, the mass fraction of the solute in the polycationic polymer solution is 1-30%, and the mass fraction of the solute in the polyanionic polymer solution is 1-30%. In a more preferred embodiment, the mass fractions of the solute in the polycationic polymer solution and the polyanionic polymer solution are the same.

[0041] In some embodiments, the negatively charged porous membrane is immersed in the polycationic polymer solution and the polyanionic polymer solution for 2 to 20 minutes at a temperature of 15 to 50° C. In a more preferred embodiment, the immersion time is 10 to 15 minutes at a temperature of 25 to 35° C.

[0042] In some embodiments, the negatively charged porous membrane is immersed in a polycationic polymer solution or a polyanionic polymer solution under an ultrasonic environment, the ultrasonic time is 5 to 10 min, the ultrasonic frequency is 20 to 80 KHz, and the preferred ultrasonic frequency is 20 to 40 KHz.

[0043] In some embodiments, steps S2 and S3 are repeated to alternately form multiple layers of the first coating layer and the second coating layer, the sum of the number of the first coating layer and the number of the second coating layer is the total number of layers, and the total number of layers is 2 to 30 layers.

[0044] In the steps of forming the first coating and the second coating, the functional diaphragm of the zinc-bromine liquid flow battery of the present application adopts an ultrasonic-assisted mixed liquid impregnation method, which can help the solution enter the pores of the porous diaphragm, and the charged polymer electrolyte is adsorbed in the pores by electrostatic action. Its hydrophilic and charged ionic groups can greatly reduce the surface energy of the porous diaphragm, provide reaction sites for the active substances in the aqueous electrolyte of the zinc-bromine liquid flow battery, and reduce the interface resistance; on the other hand, the ionic groups have strong ion exchange capacity, which can reduce the resistance of the porous diaphragm itself. The two factors promote each other, thereby reducing the resistance of the zinc-bromine liquid flow battery and improving the energy efficiency of the battery.

[0045] In some embodiments, the drying method can be any one of natural air drying, forced air low-temperature drying, vacuum low-temperature drying, freeze drying, and titanium dioxide supercritical drying.

[0046] The preferred drying method is freeze drying, with a vacuum degree of 100-1000 Pa, a temperature of -50-5 °C, and a drying time of 5-10 h. Compared with the traditional oven drying method, freeze drying avoids the collapse of the pore structure caused by the rapid volatilization of the solvent during the drying process, resulting in a decrease in the porosity of the porous membrane and an increase in resistance.

[0047] In some embodiments, the porous membrane is any one of a polypropylene microporous membrane, a polyethylene microporous membrane, a polycarbonate microporous membrane, a polyacrylonitrile microporous membrane, a polyethersulfone microporous membrane, a polyimide microporous membrane, and a polyvinylidene fluoride microporous membrane. Preferably, the porous membrane is a polyvinylidene fluoride microporous membrane with a pore size of 30 to 100 nm, a porosity of 40% to 75%, a micropore thickness of 0.3 to 1.0 mm, and a static water contact angle of 100 to 110°.

[0048] In some embodiments, the zinc-bromine flow battery functional diaphragm prepared by the technical solution of the present application achieves a pore size of 20-50 nm, a porosity of 40%-60%, a diaphragm static water contact angle of 50-100°, and a resistivity of 0.4-1.0 Ω·dm. More preferably, by increasing the number of total layers, the pore size of the porous diaphragm is reduced to 12 nm, and the diaphragm static water contact angle is reduced to 50°.

[0049] Example 1 S1: ultrasonically clean the polyvinylidene fluoride porous membrane in acetone, anhydrous ethanol and deionized water in sequence, dry it in a forced air oven at 60°C to obtain a pretreated porous membrane, and pickle the pretreated porous membrane with mixed acid, wherein the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, the pickling temperature is 50°C, and the treatment time is 10 min, so that the pretreated porous membrane is modified to have a negative charge, thereby obtaining a negatively charged porous membrane; S2: Prepare a 1% polyaniline solution and a 1% polyacrylamide solution, first ultrasonically immerse the negatively charged porous membrane in the polyaniline solution for 10 min at a temperature of 20 °C, an ultrasonic frequency of 20 HKz, and an ultrasonic time of 8 min, then wash the surface with deionized water and dry to form a first coating; S3: immersing the porous membrane with the first coating in a polyacrylamide solution for 10 min at a temperature of 20 °C, an ultrasonic frequency of 20 HKz, and an ultrasonic time of 8 min, washing the surface with deionized water and drying to form a second coating; S4: The porous membrane with a total of 2 layers of coating was freeze-dried at a vacuum degree of 500 Pa, a temperature of -50°C, and a drying time of 5 h to obtain a zinc-bromine liquid flow battery functional membrane.

[0050] Example 2 The polyvinylidene fluoride porous membrane in step S1 is replaced with a polyethylene porous membrane; Step S4 is adjusted as follows: alternately repeating steps S2 and S3 to alternately form a first coating layer and a second coating layer on the outside of the negatively charged porous membrane until the total number of the first coating layer and the second coating layer is 10 layers, and the outermost layer is the second coating layer, and freeze-drying the porous membrane with a total number of 10 layers at a vacuum degree of 500 Pa, a temperature of -50 °C, and a drying time of 5 h to obtain a zinc-bromine liquid flow battery functional membrane; The remaining steps are consistent with the preparation steps in Example 1.

[0051] Example 3 The polyvinylidene fluoride porous membrane in step S1 is replaced by a polyetheretherketone porous membrane, a 5% polyaniline solution and a 5% polyacrylamide solution are prepared in step S3, and the remaining preparation steps are consistent with the preparation steps in Example 2.

[0052] Example 4 Step S4 is adjusted to alternately set the first coating layer and the second coating layer with a total of 18 layers, and the remaining preparation steps are consistent with the preparation steps in Example 1.

[0053] Example 5 After the pretreated porous membrane is obtained in step S1, ozone treatment is used to make the pretreated porous membrane have a negative charge, the ozone concentration is 0.1 ppm, and the treatment time is 10 min; In step S3, a polyaniline solution with a concentration of 5% and a polyacrylamide solution with a concentration of 5% are respectively prepared, and step S4 is adjusted to alternately set a first coating layer and a second coating layer with a total of 26 layers. The remaining preparation steps are consistent with the preparation steps in Example 1.

[0054] Example 6 In step S3, a polyaniline solution with a concentration of 10% and a polyacrylamide solution with a concentration of 10% are respectively prepared, and step S4 is adjusted to alternately set a first coating layer and a second coating layer with a total of 18 layers. The remaining preparation steps are consistent with the preparation steps in Example 1.

[0055] Example 7 In step S3, a polyaniline solution with a concentration of 15% and a polyacrylamide solution with a concentration of 15% are respectively prepared, and step S4 is adjusted to alternately set a first coating layer and a second coating layer with a total of 18 layers. The remaining preparation steps are consistent with the preparation steps in Example 1.

[0056] Comparative Example 1 In step S1, the porous membrane is cleaned to obtain a pretreated porous membrane, which is not charged by any treatment method. That is, a polyaniline solution and a polyacrylamide solution are immersed on the outside of the pretreated porous membrane to form a coating and dry it to obtain the zinc-bromine liquid flow battery membrane of Comparative Example 1.

[0057] Comparative Example 2 After step S1 is completed, a negatively charged porous membrane is obtained without forming a coating on the outside thereof, which is used as the zinc-bromine liquid flow battery membrane of comparative example 2.

[0058] Comparative Example 3 Polyvinylidene fluoride without any treatment was used as the zinc-bromine flow battery separator in comparative example 3.

[0059] Performance Testing 1. The porous membranes prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were respectively subjected to pore size test, porosity test, resistivity test and static water contact angle test. In order to present the test results more clearly, the membrane coating formulas and performance test results of the embodiments and comparative examples were accurately recorded in Tables 1 and 2.

[0060] 2. Example 5 and Comparative Example 3 were subjected to capillary method, mercury injection method, gas-liquid method and liquid-liquid method pore size tests respectively. In the liquid-liquid method test of the diaphragm, the infiltrated liquid was isobutanol, and the displacement liquid was a saturated solution of isobutanol and deionized water; the diaphragm was cut into samples with a diameter of 40 mm using a cutter, placed in the test cavity, and the cavity was gradually pressurized, and the pressure P and the flow rate L of the displacement liquid were accurately recorded, where the pressure corresponding to the intersection of the semi-dry line and the wet line was the pressure of the average pore size, and then the pressure data was converted into pore size data according to the capillary conversion formula to obtain the average pore size. The results of the pore size test are recorded in Table 3.

[0061] Table 1 Performance test results of various embodiments

[0062] The results of analyzing Examples 1 to 7, gradually increasing the concentration of polycationic polymer solution, polyanionic polymer solution and the total number of coatings, and the performance test results of the zinc-bromine flow battery diaphragm show that the pore size and static water contact angle of the diaphragm gradually decrease, and the porosity of the diaphragm continues to decrease. With the increase in the concentration of polycationic polymer and polyanionic polymer, the total amount of electrolyte in the impregnation solution increases, which enhances the ion exchange capacity of the diaphragm, compensates for the loss of increased resistivity caused by the decrease in pore size and porosity, and makes the overall resistivity of the diaphragm almost unchanged.

[0063] In Example 6 and Example 7, the concentrations of polycationic polymers and polyanionic polymers were further increased. Although the pore size of the membrane decreased, it is speculated that the porosity of the membrane decreased significantly due to the high concentration, and the hydrophilicity was almost unaffected, so the overall resistivity of the membrane increased significantly.

[0064] Table 2 Performance test results of Example 1 and Comparative Examples 1 to 3

[0065] The diaphragm of Comparative Example 1 was not negatively charged, the diaphragm of Comparative Example 2 was not coated, and the diaphragm of Comparative Example 3 was the original polyvinylidene fluoride membrane. Analysis of the performance test results in Table 2 shows that the resistivity and static water contact angle of the diaphragm were greatly reduced after acidification treatment, indicating that the activation treatment of the diaphragm and the layer-by-layer self-assembled polymer electrolyte can enhance the hydrophilicity and ion transmission capacity of the diaphragm.

[0066] As a comparative supplement, the zinc-bromine liquid flow battery membrane of Example 5 and the zinc-bromine liquid flow battery membrane of Comparative Example 3 were subjected to pore size tests using the capillary method, mercury injection method, gas-liquid method and liquid-liquid method, and the test results are recorded in Table 3 below. Figure 1 and Figure 2 The capillary method test pore size distribution diagrams of Example 5 and Comparative Example 3 are respectively, Figure 3 and Figure 4 The pore size distribution diagrams of the mercury intrusion method test of Example 5 and Comparative Example 3 are respectively, Figure 5 and Figure 6 The pore size distribution diagrams of the gas-liquid method test of Example 5 and Comparative Example 3 are respectively, Figure 7 and Figure 8 The pore size distribution diagrams of the liquid-liquid method test of Example 5 and Comparative Example 3 are shown respectively.

[0067] Table 3 Aperture test results of Example 5 and Comparative Example 3

[0068] Analyzing the pore size test results in Table 3, in the pore size test results of various methods, the average pore size of the zinc-bromine flow battery functional membrane of Example 5 is smaller than the average pore size of the membrane of Comparative Example 3, and the proportion of blind holes is reduced from 36.72% to 18.7%, and the proportion of blind holes is effectively improved, which shows that the technical method of the present application effectively reduces the average pore size and the proportion of blind holes of the membrane through the first coating and the second coating assembled layer by layer, and reduces the risk of electrolyte penetrating the blind holes of the flow battery membrane during repeated charging and discharging of the battery.

[0069] The zinc-bromine flow battery membranes of Example 5 and Comparative Example 3 were tested by SEM electron microscope. The test results are as follows: Fig. 9 and Fig.10 As shown, polycationic polymers and polyanionic polymers can be well filled in the pores of the diaphragm, effectively reducing the average pore size and the proportion of blind holes.

[0070] The zinc-bromine liquid flow battery functional diaphragm of the present application prolongs the service life of the functionalized diaphragm in the zinc-bromine liquid flow battery through the improvement of the diaphragm structure design and the preparation method, thus providing a basis for the broad commercial prospects of the zinc-bromine liquid flow battery.

[0071] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A zinc-bromine flow battery functional diaphragm, characterized in that: It includes a negatively charged porous membrane, and multiple first coatings and multiple second coatings alternately arranged on the outside thereof, wherein the first coating is positively charged and the second coating is negatively charged, and the outermost layer of the zinc-bromine liquid flow battery functional membrane is the second coating, and the sum of the number of the first coating and the second coating is not less than 2.

2. The zinc-bromine flow battery functional diaphragm according to claim 1, characterized in that: The porous membrane is treated with plasma, ozone, ultraviolet light or mixed acid pickling to make it negatively charged, thereby obtaining the negatively charged porous membrane.

3. The zinc-bromine flow battery functional diaphragm according to claim 1, characterized in that: The sum of the number of the first coating layer and the number of the second coating layer is 2 to 30.

4. A method for preparing a functionalized diaphragm for a zinc-bromine flow battery, characterized in that: The method comprises the following preparation steps: S1: pre-treating the porous membrane to form a porous membrane with negative charge; S2: preparing a polycationic polymer solution and a polyanionic polymer solution, immersing the negatively charged porous separator in the polycationic polymer solution, and forming a first coating after drying; S3: immersing the porous membrane having the first coating layer in the polyanionic polymer solution to form a second coating layer after drying; S4: Repeat the steps S2 and S3 as required to form a plurality of alternating first coatings and second coatings, and the outermost layer is the second coating, and the zinc-bromine liquid flow battery functionalized diaphragm is obtained after freeze-drying.

5. The method for preparing a functionalized diaphragm for a zinc-bromine flow battery according to claim 4, characterized in that: The porous membrane is made negatively charged by any method of plasma treatment, ozone treatment, ultraviolet light treatment or mixed acid pickling to form the porous membrane with negative charge.

6. The method for preparing a functionalized diaphragm for a zinc-bromine flow battery according to claim 4, characterized in that: The polycationic polymer solution is a solution of the following substances: polyaniline, polyethyleneimine, polydiallyldimethylammonium chloride, polypyrrole, and chitosan.

7. The method for preparing a functionalized diaphragm for a zinc-bromine flow battery according to claim 6, characterized in that: The polyanion polymer solution is a solution of the following substances: tannic acid, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyamic acid, polyamic acid salt, perfluorosulfonic acid, polystyrene sulfonate, polyarylether sulfone sulfonate, and polyarylether sulfone ketone sulfonate.

8. The method for preparing a functionalized diaphragm for a zinc-bromine flow battery according to claim 7, characterized in that: The mass fraction of the solute in the polycationic polymer solution is 1-30%, and the mass fraction of the solute in the polyanionic polymer solution is 1-30%.

9. The method for preparing a functionalized diaphragm for a zinc-bromine flow battery according to claim 4, characterized in that: In step S1, the porous membrane is cleaned to obtain a pretreated porous membrane, and the pretreated porous membrane is made negatively charged to form the negatively charged porous membrane.

10. A zinc-bromine flow battery, characterized in that: It comprises the zinc-bromine liquid flow battery functionalized diaphragm as described in any one of claims 1 to 3, or the zinc-bromine liquid flow battery functionalized diaphragm prepared by the preparation method as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Composite film for flow energy storage battery and application thereof

    CN102867928A

  • Application of basic porous membrane in liquid flow energy storage battery

    CN103682212A

  • Method for improving hydrophilicity and thermal stability of polypropylene lithium-ion battery separator

    CN103992505A

  • Difunctional composite porous membrane and preparation and application thereof

    CN104300101A

  • Piezoresistive / piezoelectric interlayer material and preparation and application methods thereof, and interlayer type sensor and preparation and application methods thereof

    CN105953821A

Cited By

  • Heterogeneous polyelectrolyte self-assembled membrane as well as preparation method and application thereof

    CN120109248A

  • Heterogeneous polyelectrolyte self-assembly film, preparation method and application thereof

    CN120109248B